2009
DOI: 10.1158/1078-0432.ccr-08-0989
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis and Prognostic Effect of Cancer-Testis Antigen Expression in Multiple Myeloma

Abstract: Purpose: Reliable data on the persistence of tumor expression of cancer-testis (CT) antigens over time and consequent analyses of the effect of CT antigen expression on the clinical course of malignancies are crucial for their evaluation as diagnostic markers and immunotherapeutic targets. Experimental Design: Applying conventional reverse transcription-PCR, real-time PCR, and Western blot, we did the first longitudinal study of CT antigen expression in multiple myeloma analyzing 330 bone marrow samples from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 35 publications
(23 reference statements)
3
82
1
12
Order By: Relevance
“…CTA expression in myeloma has been evaluated in large patient sets but emphasis has so far been on newly diagnosed patients. 13,16,29,30 Compared to the study of Condomines et al, 16 presence of gene expression frequency differed no more than 2-fold in 73% of overlapping genes when compared to the frequencies found in newly diagnosed patients in our study. Of these, 12 are highly correlated with a difference in frequency of no more than 1.5-fold, including MAGEC1, MAGEA5 and SSX3; 61%, 26% and 3% in our study and 66%, 22% and 3% in the study of Condomines et al 16 In some cases, different probe sets belonging to the same gene may explain the difference in expression frequencies between the two studies.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…CTA expression in myeloma has been evaluated in large patient sets but emphasis has so far been on newly diagnosed patients. 13,16,29,30 Compared to the study of Condomines et al, 16 presence of gene expression frequency differed no more than 2-fold in 73% of overlapping genes when compared to the frequencies found in newly diagnosed patients in our study. Of these, 12 are highly correlated with a difference in frequency of no more than 1.5-fold, including MAGEC1, MAGEA5 and SSX3; 61%, 26% and 3% in our study and 66%, 22% and 3% in the study of Condomines et al 16 In some cases, different probe sets belonging to the same gene may explain the difference in expression frequencies between the two studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Atanackovic et al reported on the longitudinal analysis of 4 CTA genes in 17 patients during treatment, and in most cases the expression of these genes persisted from initial presentation to relapse. 13 Only MAGEC2 demonstrated a clear reduction in terms of foldchange in our study and is also the gene which was most frequently decreased in the study of Atanackovic et al 13 The relationship between CTA expression and its prognostic value is underlined by the expression of SSX1 mentioned above. Moreover, multivariate analysis identifies SSX1 as an independent prognostic factor associated with poor overall survival in relapse cases, with CTAG2 prognostic for progression free survival in this set.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations